2013
DOI: 10.1155/2013/542736
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Loss Interventions for Hispanic Populations: The Role of Culture

Abstract: In the United States, ethnic minorities are overrepresented among the overweight and obese population, with Hispanic individuals being among the groups most at risk for obesity and obesity-related disease and disability. Most weight-loss interventions designed for the general population have been less successful with individuals from ethnic minorities and there is a pressing need to develop more effective interventions for these groups. This paper examines the importance of culture in the development of “cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 44 publications
3
79
1
3
Order By: Relevance
“…While there is a lack of studies comparing Spanish to other communities, studies in the United States showed that ethnic minorities, such us Hispanic, are overrepresented among the overweight and obese population, which highlight the importance of culture in the development of "culturally competent" weight-loss interventions [5]. …”
Section: Introductionmentioning
confidence: 99%
“…While there is a lack of studies comparing Spanish to other communities, studies in the United States showed that ethnic minorities, such us Hispanic, are overrepresented among the overweight and obese population, which highlight the importance of culture in the development of "culturally competent" weight-loss interventions [5]. …”
Section: Introductionmentioning
confidence: 99%
“…These types of health intervention programs, such as Beyond Sabor, might reduce the need for pharmacological treatments. However, few weight-loss or nutrition/exercise behavior change interventions have targeted Hispanic populations (Lindberg & Stevens, 2007). As a result, traditional approaches to obesity prevention and managing diabetes in the U.S. have been perceived by Mexican Americans, in some instances, as culturally insensitive and ineffective (Alcozer, 2000).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Although obesity is highly prevalent in Hispanics/Latinos , Hispanics have largely been underrepresented in this type of research (Lindberg & Stevens, 2007). A number of randomized controlled trials evaluating the effectiveness of interventions for reducing or treating obesity have been conducted, but few have focused on Hispanics/Latinos and a lesser number on Mexican Americans (Galani & Schneider, 2007;Glenny, O'Meara, Melville, Sheldon & Wilson, 1997;Lindberg & Stevens, 2007).…”
Section: Factors Associated With Weight Loss Successmentioning
confidence: 99%
See 1 more Smart Citation
“…These natural helpers emerge as leaders in their community and provide advice and social support (Israel, 1985). Throughout the literature, they are referred to as community health workers or promotoras and many studies confirm the efficacy of their value in bridging networks in the community (Nimmons, Beaudoin, & John, 2015;Brown & Harris, 2014) Hispanics are generally unsuccessful mainly because they ignore the food preferences and lifestyle of this population (Lindberg, Stevens, & Halperin, 2013;Lindberg & Stevens, 2007;MacClancy, 1992). This study, with its attention to culture, serves as a model for intervention design and execution in underserved minority populations, such as those in the Lower Rio Grande Valley.…”
Section: Statement Of the Problemmentioning
confidence: 99%